ANALISIS REMBESAN DI BAWAH TUBUH BENDUNGAN URUGAN - I Gusti Ngurah Putu Dharmayasa (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2018)
ABSTRACT Indonesian government has built many dams in some areas and dams that have been built mostly earth dam. Earth dam becomes an option to be built because it was easier to obtain material to build the dam. Building process can be faster. Benel Dam in Melaya sub-district, Jembrana district, Bali province which had been evaluated was an earth dam that had been built in 2010. In order to provide benefits in the long time, the control of the seepage in the dam was needed so that safety can always be monitored. Measurements that were performed to determine the safety of the dam was measurement of the seepage discharge that occurs in the foundation. Therefore it is important to calculate the seepage discharge during the rainy season because in rainy season the water level in the upstream reaches the maximum position so it will cause maximum seepage in the foundation of the dam. The analysis was performed with SEEP/W and flow-net, with no cut off condition and with cut off. The result of the analysis that has been done, the seepage discharge in the dam’s foundation without cut-off for rainy season condition calculated with SEEP/W equal to 3.162 × 10-6 m3/sec and with cut-off obtained 2.077 × 10-6 m3/sec. While seepage discharge in the foundation of the dam without cut-off for rainy season conditions calculated with flow-net obtained 3.15 × 10-6 m3/sec and with a cut-off obtained 1.85 × 10-6m3/sec discharge. The results of this calculation show that the installation of cut off can reduce the amount of seepage. The seepage that occurs in the foundation of the dam was smaller than the allowed seepage that was 4.9206 m3/sec, so that the seepage discharge through the dam's foundation was safe for the dam. Key words: earth dam, flow-net, seepage discharge